The effect of education on earnings in a post-conflict economy: Evidence from Bosnia and Herzegovina - Aida Rizvanovic; Adnan Efendic (Financial Internet Quarterly, 2021)
This paper investigates the effect of formal education on individual earnings in Bosnia and Herzegovina (BiH). We use empirical regression analysis and an extended Mincer's model, which are applied to the Labour Force Survey data from 2018. Our empirical results suggest that a higher level of both statutory and additional education has positive and statistically significant effect on higher earnings of individuals in this post-conflict society. Such a finding implies that investment in education, both statutory and additional, bring economic benefits to individuals, although this is sometimes challenged by the general public of this society. Moreover, we find that employees in the public sector record systematically higher earnings than those in the private sector, suggesting a need for strategic policies targeting this difference. The outcome of our analysis is a good indicator of productivity achieved through improved educational performance, and thus provides scientific evidence to the positive effect of human capital hypothesis in BiH.
Keywords: A20; J30; 330; education; individual earnings; human capital; Bosnia and Herzegovina